The association between serum levels of potential biomarkers with the presence of factors related to the clinical activity and poor prognosis in spondyloarthritis (2012)
Background: Serum biomarkers traditionally associated with inflammatory activity and a poor prognosis in rheumatic diseases do not show the same relationship in spondyloarthritis. Objective: To establish the association between serum levels of potential biomarkers with the presence of factors related to clinical activity and poor prognosis in spondyloarthritis. Methods: Sixty-two patients were included: 13 with reactive arthritis, 19 with ankylosing spondylitis, and 30 with undifferentiated spondyloarthritis. The results were compared with those from 46 healthy controls. Clinical, radiological, and laboratory characteristics were assessed. The results were analyzed based on the presence of uveitis, enthesitis, inflammatory back pain, arthritis, HLA-B27 and sacroiliac involvement. The analyzed biomarkers included ESR, US-CRP, SAA, LBP, FSC-M, and MMP-3; and cytokine serum levels measured were: IL-17, IL-6, IL-1α, TNF-α, IFN-γ, and IL-23. Results: Forty-three (69.4%) patients were male. The average age was 31.9 ± 9.9 years and the age at the onset of symptoms was 26.9 ± 7.3 years. HLA-B27 was positive in 26 (41.9%) patients, inflammatory back pain in 42 (67.7%), arthritis in 44 (71.0%), and enthesitis in 34 (54.8%). IL-17, IL-23, TNF-α, IL-6, IL-1α, and US-CRP levels were significantly higher in patients with SpA when compared to controls. US-CRP (P = 0.04), IL-6 (P = 0.003), IL-1α (P = 0.03), and LBP (P = 0.03) levels were associated with presence of HLA-B27, inflammatory back pain, and arthritis. Conclusion: An increase in serum levels of US-CRP, IL-6, IL-1α, and LBP was correlated with factors associated with clinical activity and poor prognosis in spondyloarthritis.